Uses of various waters and hot springs writtern about in the sources of Mongolian and Korean medicine - П.Молор-Эрдэнэ,; Хан, Жү Ён (Acta Mongolica, 2015)
The purpose of this study is to compare usages of various therapeutic waters and natural hot springs described in the four valuable medical sources of Mongolian and Korean medicine namely “Dongui bogam”, the encyclopedic scripture of medical knowledge and treatment techniques of East Asia edited by the Korean scholar Heo Jun (1539-1615), “The four medical tantra”, the principal textbook of Tibetan and Mongolian medicine, “The wonderful illumination to the understanding of knowledge”, a major sourcebook of Mongolian and Tibetan materia medica written by the Mongolian scholar Naiman Toin Jamphel Dorje (1792-1855) and “A Medicine and Medical Collection”, an important source covering the various area of Mongolian and Tibetan medicine, which was written by Mongolian scholar, Toin Lobsang Chopel in Tibetan (19th century). Descriptions about various waters and springs in the sources can be ascertained in the type, rank, taste, nature, power, effects, methods and time of use, methods of collecting, caution and regime.